2018
DOI: 10.1590/2317-4889201820180029
|View full text |Cite
|
Sign up to set email alerts
|

Favorability potential for IOCG type deposits in the Riacho do Pontal Belt: new insights for identifying prospects of IOCG-type deposits in NE Brazil

Abstract: Archean iron oxide-copper-gold (IOCG) deposits have been systematically described in the world class Carajás IOCG district, Amazonian region of Brazil. More recently, several Neoproterozoic (ca 1.13 to 0.96 Ga) IOCG deposits have been identified in the Riacho do Pontal mobile belt situated in the Borborema Province on the northern border of the São Francisco Craton. In these Neoproterozoic deposits, several copper occurrences have been mapped along shear zones. The primary hydrothermal mineral associations res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Geologic characteristics of the world-class Carajás IOCG deposits are distinct and show a complex interplay between geologic structures, fluid flows, and forms of hydrothermal alteration [12][13][14][15][16][17][18][19][20][21][22][23][24]. For example, the flow of mineralized fluids along regional shear zones is responsible for the "sigmoidal-shape" structural pattern and magnetic signature of the Carajás province and Vale do Curaçá district [6,14,20,25].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Geologic characteristics of the world-class Carajás IOCG deposits are distinct and show a complex interplay between geologic structures, fluid flows, and forms of hydrothermal alteration [12][13][14][15][16][17][18][19][20][21][22][23][24]. For example, the flow of mineralized fluids along regional shear zones is responsible for the "sigmoidal-shape" structural pattern and magnetic signature of the Carajás province and Vale do Curaçá district [6,14,20,25].…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of sulfides, however, can also occur in norite-and biotite-rich shear rocks and in calcsilicate rocks. Recently, new geologic [24,[26][27][28][29], tectonic [26,30], isotopic, and geochemical [27] studies have shown evidence that copper mineralization is related to the diverse family of IOCG deposits. In the last 10 years, high-resolution airborne geophysical surveys have been completed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations